Comparative Analysis of Flat Slab and Grid Slab in Different Seismic Zones (International Journal of Innovative Research in Computer Science & Technology, 2022)
Because of ever-increasing urbanization  and a flexuous population, there has been an increasing call  for the construction of tall buildings. Earthquakes are the  bane of such tall buildings. Because earthquake forces are  haphazard in nature and unpredictable, we want to develop  engineering tools for studying systems under the influence  of those forces. Thus, careful modeling of such earthquake  loads is required in order to examine the behavior of the  structure with a clear perspective of the harm that is  expected. Examining the structure for different earthquake  intensities, followed by exams for various criteria at each  level, has become an essential exercise over the last two  decades. [9]Earthquake-resistant design (ERD) of  construction has advanced significantly since the  preliminary thoughts took form in the early 20th century.  The invention of accelerofigure and introduction of  response spectrum are the crucial steps in the history of  ERD. The other essential development was the know-how  of ductility and hysteretic damping. Gradually, the  earthquake-resistant design has advanced considerably in  the form of capacity design, displacement based design,  and performance-based design. Earthquakes cause varying  degrees of shaking in different locations, and the damage  caused to buildings in these locations is also unique. As a  result, it is critical to build an earthquake-resistant  structure that can withstand a certain level of shaking and  absorb the impact of an earthquake. Because of the varying  depths of earthquakes, identical magnitudes of earthquakes  occur, resulting in varying destructive effects in various  regions. As a result, the seismic behavior of buildings with  comparable layouts must be understood under various  earthquake intensities. It is critical to perform seismic  evaluation of the structure using various available methods  in order to determine seismic responses. [2]
Keywords: Base shear; Bending moment; Gridslab; Nodal displacement; Shear force